2017
DOI: 10.1109/tpds.2016.2614805
|View full text |Cite
|
Sign up to set email alerts
|

Ephemeral Content Popularity at the Edge and Implications for On-Demand Caching

Abstract: Abstract-The ephemeral content popularity seen with many content delivery applications can make indiscriminate on-demand caching in edge networks highly inefficient, since many of the content items that are added to the cache will not be requested again from that network. In this paper, we address the problem of designing and evaluating more selective edge-network caching policies. The need for such policies is demonstrated through an analysis of a dataset recording YouTube video requests from users on an edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…There are several tradeoffs in this area and the choice of replacement strategy has to be fine-tuned based on the use case and the factors to be optimized. Intelligent cache insertion policies have also been proposed to take into account the long tail of one-time requests [87], [103].…”
Section: Http Cachingmentioning
confidence: 99%
“…There are several tradeoffs in this area and the choice of replacement strategy has to be fine-tuned based on the use case and the factors to be optimized. Intelligent cache insertion policies have also been proposed to take into account the long tail of one-time requests [87], [103].…”
Section: Http Cachingmentioning
confidence: 99%
“…Most existing caching works focus on replacement policies [2,26]. However, recently it has been shown that the cache insertion policies play a very important factor in reducing the total delivery costs [6,24]. Motivated by these works, this paper focuses on the delivery cost differences between different selective cache insertion policies.…”
Section: Related Workmentioning
confidence: 99%
“…This class of policies is motivated by the risk of cache pollution due to ephemeral content popularity and the long tail of one-timers (one-hit wonders) observed in edge networks [6,20,24,27]. Recent works including trace-based evaluations of cache on M th request policies [6,24]. Carlsson and Eager [6] also present simple analytic models for hit and insertion probabilities.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, content objects are added to the cache whenever they are requested and the cache does not contain a copy, and one of several cache replacement strategies is used by the proxy cache to chose whether to write over a piece of data or not. More intelligent cache insertion policies have recently been proposed to take into account the long tail of one-time requests [21], [22].…”
Section: Web Caching and Caching Of Http-based Streamsmentioning
confidence: 99%